2004
DOI: 10.1002/gps.1237
|View full text |Cite
|
Sign up to set email alerts
|

Older people with schizophrenia: a community study in a rural catchment area

Abstract: Despite significant differences in presentation, elderly patients with schizophrenia and very late onset schizophrenia-like psychosis have much in common. Both groups are vulnerable with high levels of psychopathology, poor insight, sensory impairment and social isolation. The needs of older people with schizophrenia must be taken into account when services for older adults are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…This might imply that the brains of men and women show sex-specific susceptibility of primary psychosis according to age. 34 This female dominance in the late-onset psychosis has been a consistent finding, 2,3,8,10,11,14,17,30,31,[39][40][41][42][43] and is not due to a potential social covariate like marital status, role-expectations, help-seeking behaviors and premorbid adjustment. 44 It is conceivable that estrogen is protective and its withdrawal in mid-life following menopause creates the milieu to develop late-onset psychosis.…”
Section: Risk Factorsmentioning
confidence: 80%
See 4 more Smart Citations
“…This might imply that the brains of men and women show sex-specific susceptibility of primary psychosis according to age. 34 This female dominance in the late-onset psychosis has been a consistent finding, 2,3,8,10,11,14,17,30,31,[39][40][41][42][43] and is not due to a potential social covariate like marital status, role-expectations, help-seeking behaviors and premorbid adjustment. 44 It is conceivable that estrogen is protective and its withdrawal in mid-life following menopause creates the milieu to develop late-onset psychosis.…”
Section: Risk Factorsmentioning
confidence: 80%
“…The overall assessed severity of negative symptoms in patients with late-onset psychosis compared to old patients with earlyonset psychosis, 8,37 though other studies reported no significant difference. 10,46 Especially, when psychosis develops after the age of 60 years, formal thought disorder and negative symptoms are very rare.…”
Section: Phenomenologymentioning
confidence: 92%
See 3 more Smart Citations